Challenges and Pathways in Dissemination and Adoption of Better Practices for Dairy Cattle Welfare in India (Indian Journal of Animal Production and Management, 2024)
The rapidly growing global human  population, currently at 8 billion (UN, 2022), poses  significant challenges to food and nutritional  security. Livestock, especially dairy production, has  the potential to play a transformative role in  addressing these challenges by converting low value, inedible resources into essential animal  source foods such as milk, meat, and eggs. Despite  ongoing efforts to enhance productivity in this  sector, there are growing concerns about the ethical  implications, particularly regarding animal welfare.  The rising consumer awareness and changing  attitudes toward the treatment of farm animals have  made animal welfare a crucial factor in modern  dairy farming. The welfare of dairy animals is not  only a matter of ethical concern but is also closely  linked to the efficiency of production systems and  the quality of the end products. In the Indian  context, where dairy cattle hold both economic and  cultural significance, the reality often contrasts with  the ideal, as evidenced by the high number of stray  cattle and compromised animal welfare. Addressing  these challenges is essential for the sustainability of  dairy farming, and this can be achieved through the  integration of welfare-oriented management  practices. Such practices include proper feeding,  breeding, housing, health management, and  humane handling during transportation. By  adopting these strategies, which also align with  changing consumer preferences, dairy farming can  become more sustainable and economically viable,  benefiting both animals and farmers.
Keywords: dairy farming; animal welfare; sustainable